Structural insight into PIF6-mediated red light signal transduction of plant phytochrome B - Hanli Jia; Zeyuan Guan; Junya Ding; Xiaoyu Wang; Dingfang Tian; Yan Zhu; Delin Zhang; Zhu Liu; Ling Ma; Ping Yin (Cell Discovery)
Abstract The red/far-red light receptor phytochrome B (phyB) plays essential roles in regulating various plant development processes. PhyB exists in two distinct photoreversible forms: the inactive Pr form and the active Pfr form. phyB-Pfr binds phytochrome-interacting factors (PIFs) to transduce red light signals. Here, we determined the cryo-electron microscopy (cryo-EM) structures of the photoactivated phyB-Pfr‒PIF6 complex, the constitutively active mutant phyBY276H‒PIF6 complex, and the truncated phyBNY276H‒PIF6 complex. In these structures, two parallel phyB-Pfr molecules interact with one PIF6 molecule. Red light-triggered rotation of the PΦB D-ring leads to the conversion of hairpin loops into α helices and the “head-to-head” reassembly of phyB-Pfr N-terminal photosensory modules. The interaction between phyB-Pfr and PIF6 influences the dimerization and transcriptional activation activity of PIF6, and PIF6 stabilizes the N-terminal extension of phyB-Pfr and increases the Pr→Pfr photoconversion efficiency of phyB. Our findings reveal the molecular mechanisms underlying Pr→Pfr photoconversion and PIF6-mediated red light signal transduction of phyB.